2022
DOI: 10.3390/ijerph19159364
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Trivalent Praseodymium from Tombarthite Sewage by Microtubule Ultrafiltration Reactor with Organophosphorus in Fuel Oil

Abstract: A microtubule ultrafiltration reactor (MUFR), with an organophosphorus system containing a sewage section with buffer liquid acetic acid and an enrichment section with aqua fortis liquid and organophosphorus dissolved in fuel oil, has been studied for praseodymium(III) migration. Many factors of praseodymium(III) migration using MUFR need to be explored, including hydrogen ion molarity (or pH), cinit of praseodymium(III), the different ionic strengths of rare-earth mine sewage, the volume ratio of organophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The Ho(III) Cm and steadiness of the enriched portion regularly decline while the traditional supported fluid film is used, and the Ho(III) Cm of the wastewater portion and the enriched portion remains stable when MF-OP is used. This is because the organic phosphorus in the traditional supporting fluid film is regularly lost [ 16 , 18 , 19 , 20 , 21 , 22 , 23 ], while MF-OP with organic phosphoric fluid may constantly complement the microtube microfilter with organic phosphoric fluid. The results of this study also showed that the stability of MF-OP is indeed better than that of traditional SFF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ho(III) Cm and steadiness of the enriched portion regularly decline while the traditional supported fluid film is used, and the Ho(III) Cm of the wastewater portion and the enriched portion remains stable when MF-OP is used. This is because the organic phosphorus in the traditional supporting fluid film is regularly lost [ 16 , 18 , 19 , 20 , 21 , 22 , 23 ], while MF-OP with organic phosphoric fluid may constantly complement the microtube microfilter with organic phosphoric fluid. The results of this study also showed that the stability of MF-OP is indeed better than that of traditional SFF.…”
Section: Resultsmentioning
confidence: 99%
“…This is on account of the revival influence of organic phosphoric fluid on microtubes and when the dispersion movement of Ho(III) is definitive under stable test state. It can be seen from previous studies that the mass transfer driving force caused by diffusion equilibrium controls the collection process of the system [ 14 , 17 , 18 , 19 , 20 ]. PH value of 4.60 has been chosen as the prime pH in this test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation